Production Potentials and Economic Feasibility of Improved Sugarcane Based Cropping Systems (Indian Journal of Extension Education, 2012)
On-farm trials (OFT) were carried out on farmers’ fields in Lucknow district of Uttar Pradesh during 2005-06 and 2006-07 with a view to assess the production potentials and economic feasibility of improved sugarcane based cropping system under real farming situations. In general, sugarcane based inter-cropping system was found more productive and remunerative than the system of sole cane cropping being adopted by the farmers in general in the region. Results of OFT indicated that inter-crops viz. mustard, toria and coriander in autumn sugarcane and green gram and black gram in spring sugarcane gave considerably higher net returns over sole cropping of autumn and spring seasons cane. The inter-cropping of mustard, toria, coriander, green gram and black gram with sugarcane exhibited benefit : cost ratio of 1.35, 1.42, 1.53, 1.27 and 1.17, respectively as against 1.06, and 1.04 under the autumn sole cane and spring sole cane, respectively.